DEVELOPMENT AND SCIENTIFIC ANALYSIS OF WORD ART IN UZBEK CHILDREN’S LITERATURE - Khikmatullayeva Durdona; Yusupov Asror Raimqul ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The glorious task of Uzbek children's literature as an art of words and educational tool received special attention during the years of independence. of our republic First President I.A. Karimov's "Attention to literature - to spirituality, to the future in the "attention" guide, literature and art of words have been an expression of the people's heart since time immemorial it is emphasized that it is, among other things it is said: "Especially, we to the development of children's literature, which is extremely important for We pay special attention to the formation of independent thinking individual she always remembers that the culture of reading and reading starts from childhood we have to keep it."